Fatty acid chain length drives lysophosphatidylserine-dependent immunological outputs. Issue 8 (19th August 2021) - Khandelwal, Neha; Shaikh, Minhaj; Mhetre, Amol; Singh, Shubham; Sajeevan, Theja; Joshi, Alaumy; Balaji, Kithiganahalli Narayanaswamy; Chakrapani, Harinath; Kamat, Siddhesh S.
Summary: In humans, lysophosphatidylserines (lyso-PSs) are potent lipid regulators of important immunological processes. Given their structural diversity and commercial paucity, here we report the synthesis of methyl esters of lyso-PS (Me-lyso-PSs) containing medium- to very-long-chain (VLC) lipid tails. We show that Me-lyso-PSs are excellent substrates for the lyso-PS lipase ABHD12, and that these synthetic lipids are acted upon by cellular carboxylesterases to produce lyso-PSs. Next, in macrophages we demonstrate that VLC lyso-PSs orchestrate pro-inflammatory responses and in turn neuroinflammation via a Toll-like receptor 2 (TLR2)-dependent pathway. We also show that long-chain (LC) lyso-PSs robustly induce intracellular cyclic AMP production, cytosolic calcium influx, and phosphorylation of the nodal extracellular signal-regulated kinase to regulate macrophage activation via a TLR2-independent pathway. Finally, we report that LC lyso-PSs potently elicit histamine release during the mast cell degranulation process, and that ABHD12 is the major lyso-PS lipase in these immune cells. Highlights: Synthesis of methyl esters of lyso-PSs with varying lipid tails and their metabolism Very-long-chain lyso-PSs signal through TLR2 to cause neuroinflammation Role of long-chain lyso-PSs in macrophage signaling and mast cell degranulation ABHD12 is a major lyso-PS lipase in primary mast cells Abstract : Khandelwal et al. synthesize a library of methyl esters of lysophosphatidylserines (lyso-PSs) to facilitate rigorous structure-activity relationship studies, toward understanding the role played by the lipid tail of lyso-PSs in regulating the activation of macrophages and mast cell degranulation.